Chidamide Suppresses the Growth of Cholangiocarcinoma by Inhibiting HDAC3 and Promoting FOXO1 Acetylation - Yongpan Li; Jujia Zheng; Qiang Huo; Zhongchao Chen; Jun Chen; Xiangwei Xu (Stem Cells International)
Inhibitors for histone deacetylases (HDACs) have been identified as epigenetic drug targets to treat a variety of malignancies through several molecular mechanisms. The present study is aimed at investigating the mechanism underlying the possible antitumor effect of the HDAC inhibitor chidamide (CDM) on cholangiocarcinoma (CCA). Microarray-based gene expression profiling was conducted to predict the expression of HDACs in CCA, which was validated in clinical tissue samples from CCA patients. Next, the proliferation, migration, invasion, autophagy, and apoptosis of human CCA QBC939 and SNU308 cells were measured following treatment with CDM at different concentrations. The acetylation level of FOXO1 in the nucleus and cytoplasm of QBC939 and SNU308 cells was determined after overexpression and suppression of HDAC3. A QBC939-implanted xenograft nude mouse model was established for further exploration of CDM roles in vitro. HDAC3 was prominently expressed in CCA tissues and indicated a poor prognosis for patients with CCA. CDM significantly inhibited cell proliferation, migration, and invasion of QBC939 and SNU308 cells, while inducing their autophagy and apoptosis by reducing the expression of HDAC3. CDM promoted FOXO1 acetylation by inhibiting HDAC3, thereby inducing cell autophagy. Additionally, CDM inhibited tumor growth in vivo via HDAC3 downregulation and FOXO1 acetylation induction. Overall, this study reveals that CDM can exhibit antitumor effects against CCA by promoting HDAC3-mediated FOXO1 acetylation, thus identifying a new therapeutic avenue for the treatment of CCA.